DETERMINATION OF ETIIANOL IN ENVIRONMENTAL WATER - RUSLI, HASFANIDA (Universiti Teknologi PETRONAS, 2005)
The main objective of this research project is to determine the performance of Gas Chromatography using Flame Ionized Detector (GC/FID) and Ultra Violet visible (UV-Vis) for the analysis and quantification of ethanol. This research project is based on the development of analytical methods for enviromnental studies. Ethanol in enviromnent might be present in air, soil, and water. Ethanol is a known contaminant in enviromnental waters. Even though the concentration of ethanol is normally low in the environment, analytical methods in determining the concentration of ethanol in water need to be developed due to its effect on tumor growth hence human health in general. Once it is identified and detected, the contaminants can be removed or separate from the enviromnental waters. The scope of study for this project are to fmd the best method in terms of accuracy and precision for the analysis of ethanol in water and to use the best method identified to determine the ethanol content in enviromnental samples. From the experimental results, GC/FID has higher accuracy and precision. GC/FID is a good method in determining the lower concentration of ethanol in water. v